Assessing Service-Learning Courses in a Malaysian Higher Learning Institution: A Study of Universiti Tunku Abdul Rahman (UTAR) - Foong, Sook Ching; Kong, Kee Lok; Looi, Seow Yan; Phua, Chee Seng; Wong, Jing Man (2017)
This research will be examining the service-learning courses in Universiti Tunku Abdul Rahman (UTAR). Service-learning was originally derived from the theory of experiential education which examines in the Higher Learning Institutions (HLIs) in 1960s and 1970s (Stanton & Erasmus, 2013). Service-learning in HLIs started to become popular since early in 21st century in other nations like United State, Korea and Hong Kong (Williams, 2016; Chan, 2014; Sook, 2014). In Malaysia, the growth of HLIs like colleges and universities has led to the demand for the quality of the education which makes Malaysia as an education hub (Grapragasem, Krishnan,& Mansor, 2014). HLIs like Universiti Malaysia Kelantan and Universiti Utara Malaysia (UUM) had implemented servicelearning into their institute (Yu & Zakaria, 2012; Zahid, Jabbar, Romle, Isa,& Embi, 2015). However refer back to UTAR, there are no research being done by the researcher to assist the faculty and student to identify service-learning, yet the faculty and student may have or do not have the awareness about service-learning. Therefore, the research objective is to identify the service-learning courses offered in Bachelor of Communication (Hons) Public Relations and to measure the development of servicelearning institutionalization in Bachelor of Communication (Hons) Public Relations. The method for this research will be using mixed method which is quantitative and qualitative research method. The expected outcome for this research is to assist UTAR to evaluate service-learning industrialization.